The reality of school bullying and sports culture among high school students in the city of Hit - Awad, L.Dr. Saif Al-Din Daham; Eid, L.Dr. Anas Abdel Sattar (Sulaimani Journal for Humanities, 2026)
Bullying is a significant educational, psychological, and social problem in our society. It has become prevalent among some students who attempt to control their peers by force in order to dominate them and gain power. Participating in sports activities is a crucial factor in addressing most of the problems facing society, as it helps fill young people's free time in a beneficial way that also positively impacts the community. As secondary school teachers, the researchers observed the worsening phenomenon of bullying in schools. This problem requires addressing by all communities and institutions, especially educational ones. This research aims to identify the reality of school bullying and participation in sports activities among secondary school students in the city of Hit, and to determine the correlation between school bullying and participation in sports activities among secondary school students in Hit. The researchers employed a descriptive approach using survey methodology and correlational analysis. The research sample consisted of 336 students. The School Bullying Scale, comprising 18 items, and the Sports Participation Scale, comprising 23 items, were administered. The research yielded several conclusions, including: a negative correlation exists between school bullying and students' participation in sports activities; and participation in sports activities plays a positive role in reducing bullying behavior among students. Among the recommendations of the research are: the necessity of addressing school bullying behavior through the installation of surveillance cameras and raising educational awareness among students about its negative consequences; and the necessity of establishing playgrounds in all schools, ensuring these playgrounds are suitable for practicing multiple sports
Keywords: School bullying; participation in sports activities; high school students